The impact of decentralised forest governance: a case study from Bolivia - Jong, W. de; Becker, M.; Ruíz, S.; Gottwald, C. (2003)
The last decade has seen profound overhauls of governance in many tropical countries. Countries have adopted new economic policies, very much influenced by free-market thinking, and a reduced regulatory role of the state and its subsidiaries. This coincided with widespread decentralization of government, including natural resource governance. Bolivia is mostly known for its Andean uplands, but substantial parts of its territory are under tropical forest. Especially the economy of the northern part of the country relies for a large part on income from forest products like Brazil nuts and timber. In the middle the 1990s Bolivia enacted a set of new national laws that are affecting forest products based industries. The principal laws are several decentralization laws, a new land reform law, and a new forestry law. The new regulatory framework has resulted in a progressively larger ownership of forest land and forests by rural communities. The impact that this has on people’s livelihoods is still not entirely clear. In northern Bolivia, there is evidence that old unresolved conflicts over natural resources are erupting again. There is also evidence that some of the feudal dependency relations that existed until before the program of legal reform, are adapting themselves to the new legal framework, but not disappearing. In some places with more access to social infrastructure, a new type of forest tycoons replace the rubber and Brazil nut barons from earlier days. The local communities, new owners of forests, still have inadequate skills, knowledge and leverage that frees them from the patronage of these new rulers of the north. Political patronage by people seeking votes for public office dominates village level politics in many locations and hinders the true democratization of rural Bolivia. Despite these initial shortcomings the natural resource governance decentralization has recognizable positive outcomes. The expected positive impact, however, will need more time than initially expected.